Complete brachial plexus palsy following shoulder dislocation due to sneeze: a case report - Middleton, Austin H. (Int J Emerg Med, 2019)
BACKGROUND: Traumatic shoulder dislocation is a frequent condition presenting to the emergency department. Due to the anatomy of the shoulder, associated neurovascular damage is not uncommon. Although clinical intuition may suggest that a higher-energy mechanism is required to produce neurovascular sequelae, the existing literature does not support this supposition. CASE PRESENTATION: A 55-year-old woman presented to the emergency department with a complete brachial plexus palsy from an acute anterior shoulder dislocation following a violent sneeze. The shoulder was reduced without difficulty in the emergency department within 90 min of dislocation, and the patient was discharged. Her neurologic deficits gradually improved through a program of supervised therapy and orthopedic care. Follow-up at 1 year revealed marked improvement of motor and sensory function of the affected extremity with mild residual weakness and paresthesias in the affected hand. CONCLUSION: Neurovascular injuries in the setting of shoulder dislocation may be present despite low-energy injury mechanisms.